Implications of the novel EU AI Act for neurotechnologies - Bublitz, Jan Christoph; Molnár-Gábor, Fruzsina; Soekadar, Surjo Raphael (Neuron, 2024)
The EU AI Act, the first comprehensive regulation of AI, came into effect in August. Here, we provide an overview of the provisions that apply to the field of neurotechnology with respect to research and development and neuroscience practice and discuss some implications for the future.
Gesehen am 21.03.2025